Imenotteri Sinfiti del piano pedemontano in Lombardia I. Indagine faunistica (Hymenoptera Symphyta) (Bollettino di zoologia agraria e bachicoltura, 2024)
This paper shows the results of a study concerning Hymenoptera Symphyta of a well defined region in western Lombardy, i.e. the high plain between the Olona and Adda rivers.During the researches, on the whole performed in 36 different stations of collection, 130 sawflies species were raised; for each of them the following indications are given: a short bibliography, some informations ab out life history, the known distribution, and the italian regions where the species inhabits; then stations, dates and number of ♂♂ and ♀♀ specimens collected.The following species resulted new to Italy: Heterarthrus aceris (Kaltenbach), Empria pumila (Konow), E. baltica Conde, E. tridens (Konow), Eutomostethus punctatus (Konow), Fenusa dohrni (Tischbein), Platycampus luridiventris (Fallén), Pontania purpureae (Cameron), Nematus hypoxanthus Fòrster, N. bergmanni (Dahlbom) and N. viridis Stephens; many others species are reported for the first time from their original finding in Italy, that in some cases goes back to the last century.Some species have revealed valuable differences in respect of populations of central and northern Europe. Athalia scutellariae Cameron shows a continuous variation of colour pattern within very wide ranges, that indicates as probable the synonymy between A. scutellariae scutellariae Cameron and A. scutellariae fiammula Zhelochovtsev. A melanic form of Taxonus agrorum (Fallén) is reported; it cohabits in Piedmont and Lombardy with the typical form in a condition of balanced polymorphism. It is also mentioned that italian populations of Tenthredo campestris L. are represented for the greatest part by a light form with all the femurs yellow. Somewhat interesting facts issued from this work are besides the numerica! equality of ♂♂ and ♀♀ of Eutomostethus ephippium (Panzer) and E. luteiventris (Klug), which are represented in central and northern Europe by ♀♀ only; and vice versa the probable emergence of obligate parthenogenesis in the southern regions of the distribution area of Priophorus moria Lepeletier.It is emphasized, at last, the requirement to consider the problem of intra-specific differentiation of italian sawflies, that could else give rise to unsatisfactory taxonomic treatments.